Imaging features of Benign Perianal lesions. Issue 5 (1st August 2019) - O'Neill, Damien C; Murray, Timothy E; Thornton, Eavan; Burke, John; Dunne, Ruth; Lee, Michael J; Morrin, Martina M
Summary: Magnetic resonance imaging provides detailed visualisation, identification and extent assessment of many anal disorders. While many studies are performed in the evaluation of malignant processes such as anorectal carcinoma, the primary focus of this pictorial review is benign lesions, which involve the anal canal and perianal spaces. This pictorial review will illustrate the MRI appearances of a variety of benign conditions, which predominantly affect the anal canal, including abscess, fistulae, lipomas, developmental cysts and inflammatory conditions. MRI aids in the identification and characterisation of these abnormalities, of coexisting complications and differentiation from other perineal abnormalities. This pictorial review highlights the spectrum of non‐malignant processes involving the perianal region.